An Unusual Homicide: A case of sharp force fatality by broken glass bottle (Journal of Forensic Medicine & Toxicology, 2026)
As sharp force injury accounts for 10-20% of clinical forensic examinations, forensic pathologists are often asked to inves tigate deceased victims of stab wounds. Moreover, homicides by sharp force (stabbing and incisions) generally involve  domestic or interpersonal conflicts. Death due to stabbing is usually caused by exsanguinating incisions to organs or large  blood vessels, leading to hemorrhagic shock. This paper aims to emphasize the importance of a thorough autopsy pro cedure which includes documentation of the type, pattern and dimensions of injuries, in these cases. In the present case,  the dead body of a 40 years old unknown male was brought to the mortuary, with a history of homicidal stab over the  neck by broken beer bottles. The fatal injuries were two stab injuries over the neck, but numerous incised wounds were  also present, all injuries having atypical appearance and varied morphology. This case is discussed in light of the pattern  of injuries caused by the broken glass bottle.
Keywords: sharp force; stab on the neck; vascular injury; atypical incised wound; broken glass bottle injuries